Alleviation of Chilling Injury in Jujube Fruit (Ziziphus jujuba Mill) by Dipping in 35 ˚C Water - Promyou, Surassawadee; Supapvanich, Suriyan; Boodkord , Boontarik; Thangapiradeekajorn, Methinee (Agriculture and Natural Resources, 2012)
The purpose of this study was to investigate the effect of mild hot water immersion on the chilling injury and certain physicochemical changes in jujube fruit (Ziziphus jujuba Mill) during refrigerated storage. The fruit were immersed in hot water at 35 ˚C for 0, 10, 20 and 30 min and then stored at 4 ± 1 ˚C for 20 d. The chilling injury score and electrolyte leakage of hot-water-treated jujube fruit were lower than those of the untreated fruit. The weight loss of all treatments increased throughout storage and immersion in hot water reduced the fresh weight loss and improved the texture. The lightness (L* value) of the hot-water-treated fruit was higher and the greenness (a* value) of the hot-water-treated fruit was slightly lower than that of the untreated fruit over the storage period. Hot water immersion for 10 min inhibited the increase in activity of polyphenol oxidase (PPO) and lipoxygenase (LOX) and inhibited the increase in the malondialdehyde (MDA) content in the peel of the jujube fruit during storage when compared to the untreated fruit. The total phenolic content and the total antioxidant capacity decreased with storage time. The total phenolic content and the antioxidant capacity of the jujube fruit immersed in the hot water for 10 min were higher than those of other treatments. In conclusion, water immersion at 35 ˚C for 10 min effectively maintained the quality and reduced the chilling injury of jujube fruit during refrigerated storage.